2020
DOI: 10.3389/fmicb.2020.00043
|View full text |Cite
|
Sign up to set email alerts
|

RcLS2F – A Novel Fungal Class 1 KDAC Co-repressor Complex in Aspergillus nidulans

Abstract: The fungal class 1 lysine deacetylase (KDAC) RpdA is a promising target for prevention and treatment of invasive fungal infection. RpdA is essential for survival of the most common airborne mold pathogen Aspergillus fumigatus and the model organism Aspergillus nidulans. In A. nidulans, RpdA depletion induced production of previously unknown small bioactive substances. As known from yeasts and mammals, class 1 KDACs act as components of multimeric protein complexes, which previously was indicated also for A. ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 80 publications
(111 reference statements)
0
10
0
Order By: Relevance
“…The members of the Set3C corresponding TIG1 complex from M. oryzae have also been implicated in virulence [63]. Although Hos2 and Hda1 have been shown to be part of an Rpd3L expanded complex in S. cerevisiae and S. pombe [66], the Aspergillus nidulans Hos2 ortholog HosA was never identified by tandem affinity purifications (TAPs) with RpdA as bait [67]. RpdA TAP in A. nidulans, however, led to the identification of a new complex termed RcLS2F [67].…”
Section: The Fungal Kdac Repertoire: More Than Just the Number Of Enzymesmentioning
confidence: 99%
See 3 more Smart Citations
“…The members of the Set3C corresponding TIG1 complex from M. oryzae have also been implicated in virulence [63]. Although Hos2 and Hda1 have been shown to be part of an Rpd3L expanded complex in S. cerevisiae and S. pombe [66], the Aspergillus nidulans Hos2 ortholog HosA was never identified by tandem affinity purifications (TAPs) with RpdA as bait [67]. RpdA TAP in A. nidulans, however, led to the identification of a new complex termed RcLS2F [67].…”
Section: The Fungal Kdac Repertoire: More Than Just the Number Of Enzymesmentioning
confidence: 99%
“…Although Hos2 and Hda1 have been shown to be part of an Rpd3L expanded complex in S. cerevisiae and S. pombe [66], the Aspergillus nidulans Hos2 ortholog HosA was never identified by tandem affinity purifications (TAPs) with RpdA as bait [67]. RpdA TAP in A. nidulans, however, led to the identification of a new complex termed RcLS2F [67]. The RcLS2F complex represses genes in a KDAC activity-dependent manner and is essential for sexual reproduction [67].…”
Section: The Fungal Kdac Repertoire: More Than Just the Number Of Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have shown that class I HDACs function as members of protein complexes in vitro . For example, in filamentous fungi, RpdA interacted with RcLS2F in A. nidulans ( Bauer et al, 2020 ). Rpd3L-like HDAC complex in Fusarium Pseudograminearum contained multiple partners including FpDep1, FpSds3, FpSin3, FpRpd3, FpRxt3, FpCti6, FpPho23, and FpUme6 ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%